476 Technical and Clinical Outcomes in Concurrent Multivessel Occlusions Treated With Mechanical Thrombectomy: Insights from the STAR Collaboration. (April 2023) - Saad, Hassan Wajih; Eshraghi, Sheila; Howard, Brian M.; Buster, Bryan Edward; Akbik, Feras; Maier, Ilko; Goyal, Nitin; Starke, Robert M.; Rai, Ansaar; Fargen, Kyle Michael; Psychogios, Marios; Jabbour, Pascal; et al.
Abstract : INTRODUCTION: Endovascular thrombectomy(EVT) has become the mainstay treatment of large vessel occlusion, however its role in the treatment of patients with simultaneous multi-territory occlusions(MVOs) has not been established. METHODS: We reviewed the STAR registry and included patient data from 35 stroke centers for EVT performed to treat bilateral anterior or concurrent anterior and posterior circulation occlusions from 2017-2020. RESULTS: We included a total of 7723 patients who underwent EVT for acute ischemic stroke. 54 patients (0.7%) underwent EVT for MVOs (mean age 69 ± 12.5; Female 50%). 28% had bilateral and 72% had concurrent anterior and posterior circulations occlusions. We used propensity score matching to match patients with MVOs to another group with single vessels occlusions by age, gender, race, admission NIHSS, baseline mRS score, onset to groin, use of IV-tPA. The rate of recanalization (TICI2B/3), complications, modified Rankin score at 90 days, and mortality was not significantly different between the 2 groups. Multivariate analysis confirmed that MVOs was not a predictor of poor functional outcome, increased symptomatic hemorrhage, or longer procedure time. CONCLUSIONS: Compared to single vessel occlusions, EVT in appropriately selected MVOs has similar efficacy and safety profile.